Probing the promiscuity of ent-kaurene oxidases via combinatorial biosynthesis - Mafu, Sibongile (Proc Natl Acad Sci U S A, 2016)
The substrate specificity of enzymes from natural products’ metabolism is a topic of considerable interest, with potential biotechnological use implicit in the discovery of promiscuous enzymes. However, such studies are often limited by the availability of substrates and authentic standards for identification of the resulting products. Here, a modular metabolic engineering system is used in a combinatorial biosynthetic approach toward alleviating this restriction. In particular, for studies of the multiply reactive cytochrome P450, ent-kaurene oxidase (KO), which is involved in production of the diterpenoid plant hormone gibberellin. Many, but not all, plants make a variety of related diterpenes, whose structural similarity to ent-kaurene makes them potential substrates for KO. Use of combinatorial biosynthesis enabled analysis of more than 20 such potential substrates, as well as structural characterization of 12 resulting unknown products, providing some insight into the underlying structure–function relationships. These results highlight the utility of this approach for investigating the substrate specificity of enzymes from complex natural products’ biosynthesis.